High frequency ultrasound assesses transient changes in cartilage under osmotic loading - Zatloukalova, Jana; Raum, Kay (Mathematical biosciences and engineering, 2020)
High-frequency ultrasound is used in this study to measure noninvasively, by means of osmotic loading, changes in speed of sound and cartilage thickness caused by variations of the salt concentration in the external bath. Articular cartilage comprises three main structural components: Water, collagen fibrils and proteoglycan macromolecules carrying negative charges. The negatively charged groups of proteoglycans attract cations and water into tissue and govern its shrinkage/swelling behavior, which is a fundamental mechano-electrochemical function of cartilage tissue. In this study, the mechano-electrochemical behavior of cartilage is modeled by a diffusion model. The proposed model enables simulations of cartilage osmotic loading under various parameter settings and allows to quantify cartilage mechanical properties. This theoretical model is derived from the kinetic theory of diffusion. The objectives of the study are to quantify time dependent changes in cartilage thickness, and in speed of sound within tissue with help of the finite element based simulations and data from experiments. Experimental data are obtained from fresh and trypsinized ovine patella samples. Results show that the proposed diffusion model is capable to describe transient osmotic loading of cartilage. Mean values and their deviations of the relative changes of cartilage characteristics in response to chemical loading are presented.
Keywords: fixed charge density; Ultrasonography; numerical simulations; Cartilage, Articular; high-frequency ultrasound; osmóza; Osmosis; ovce; kloubní chrupavka; articular cartilage; Sheep; swelling behavior; Models, Biological; proteoglykany; diffusion model; osmotic loading; Animals; Proteoglycans; biologické modely; zvířata; ultrasonografie